The Limitations of Language - Moore, Terence. author. aut Link
VIII, 180 p.
Keywords: This book explores the relation between language and our senses and emotions, taking readers into domains as diverse as wine-tasting, marriage guidance counselling, medical training and face recognition. The authors suggest that language is capable of both confusing and clarifying.